Importance of haemonchosis in lamb rearing in a subhumid environment in Kenya: Preliminary results - Bullerdieck, P.; Peters, Kurt J.; Thorpe, W.R. (Research Inst. for Animal Husbandry, 1990)
Presents results of a study carried out in three locations in the Mombasa region along the Kenyan coast on haemonchosis in lambs. In the study, purebred Dorper and Maasai-Dorper F1 cross lambs were observed for their reaction to helminth infestation and the effects of anthelmintic treatment and supplementary feeding on such worm infestation. Includes data on daily weight gain and PCV (Packed Cell Volume) over age periods, weight gain under different anthelminticic treatment, and mortality rate.